Comparison Principles for Some Fully Nonlinear Sub-Elliptic Equations on the Heisenberg Group (Analysis in Theory and Applications, 2019)
In this paper, we prove a form of the strong comparison principle for a class of fully nonlinear subelliptic operators of the form $ abla^2_{H,s}ψ + L(·,ψ, abla_{H}ψ)$ on the Heisenberg group, which include the CR invariant operators.
Keywords: Comparison principle; subellipticity; CR invariance; Heisenberg group; propagation of touching points.